Validity and Practically of Learning Resources Flipbook Identification of Basidiomycota Mushrooms for Senior High School Students - Fajrul Falah; Sifak Indana; Tukiran (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The aim of this research is to describe validity flipbook type e-book in terms of the feasibility content, language, and display; and describe the practicality of an e-book in terms of an implementation observation. The method used in this study is a modified research and development method and was carried out at the Postgraduate Science Education, the State University of Surabaya in February 2020 - August 2021. The data collection technique was carried out using the validation method and the implementation observation method. The assessment instrument uses a validation sheet and an implementation observation sheet. The validity of the flipbook type e-book is reviewed from the feasibility of the content, the feasibility of the language, and the feasibility of the display. The validity of the flipbook-type e-book was assessed by three validators which included two biology lecturers and one biology teacher. For practicality, use the implementation observation sheet in terms of the use of flipbooks during the learning process. The observation sheet contains statements that will be filled out by four observers. Data analysis was carried out quantitatively. The developed e-book was tested on 20 students of class X Senior High School students in August 2021. The validation results of the flipbook type e-book by three validators obtained an average score of 3.84 with a very valid category. Based on practicality in terms of implementation, flipbooks get an average percentage of 87.2%. Thus, the flipbook-type e-book on the identification of Basidiomycota fungi is declared valid and practical.